Vicarious Warfare : American Strategy and the Illusion of War on the Cheap - Waldman, Thomas, 1980- (Book collections on Project MUSE., 2021)
This compelling account charts the historical emergence of vicarious warfare and its contemporary prominence. It contrasts its tactical advantages with its hidden costs and potential to cause significant strategic harm.